1999
DOI: 10.1038/sj.onc.1202410
|View full text |Cite
|
Sign up to set email alerts
|

C-myc overexpression and p53 loss cooperate to promote genomic instability

Abstract: p53 monitors genomic integrity at the G1 and G2/M cell cycle checkpoints. Cells lacking p53 may show gene ampli®cation as well as the polyploidy or aneuploidy typical of many tumors. The pathways through which this develops, however, are not well de®ned. We demonstrate here that the combination of p53 inactivation and c-myc overexpression in diploid cells markedly accelerates the spontaneous development of tetraploidy. This is not seen with either N-myc or L-myc. Tetraploidy is accompanied by signi®cantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
138
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 59 publications
13
138
1
Order By: Relevance
“…Six (55%) of 11 G:C-to-A:T transitions occurred at CpG dinucleotides in five hot-spot codons (175, 245, 248, 273, and 282), and it was suggested that specific p53 mutations participate in the progression of human prostate cancer and may be predictive of metastasis (10). This study, in addition to some other recent studies (both in vitro and in vivo), has demonstrated correlation between loss or mutation of p53 and the presence of CI (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). More recently, centrosome hyperamplification was found to be the major mechanism responsible for CI in vitro and in vivo (58, 59, 64 -66).…”
Section: Figure 2 P53 Ihc (Do7)supporting
confidence: 63%
“…Six (55%) of 11 G:C-to-A:T transitions occurred at CpG dinucleotides in five hot-spot codons (175, 245, 248, 273, and 282), and it was suggested that specific p53 mutations participate in the progression of human prostate cancer and may be predictive of metastasis (10). This study, in addition to some other recent studies (both in vitro and in vivo), has demonstrated correlation between loss or mutation of p53 and the presence of CI (53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). More recently, centrosome hyperamplification was found to be the major mechanism responsible for CI in vitro and in vivo (58, 59, 64 -66).…”
Section: Figure 2 P53 Ihc (Do7)supporting
confidence: 63%
“…It has been established in human tumors that deregulation of cyclin B1 is correlated, at least acutely, with negative p53 status (Innocente et al, 1999;Cui and Donehower, 2000;Krause et al, 2000;Park et al, 2000;Yin et al, 2001;Yu et al, 2002). In these tumors cyclin B1 is both deregulated with respect to the cell cycle and is massively overexpressed, even to the point where misfolded protein is processed and presented at the cell surface to invoke an immune response (Covini et al, 1997;Yu et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…c-myc abnormalities have been found to act alone or in concert with p53 abnormalities to promote genetic instability (56 -59). Of note, it has recently been reported that the inactivation of wild type p53 in cells that overexpress c-myc accelerates the emergence and overgrowth of stable tetraploid cell sublines (59). The clinical relevance of this observation is supported by findings in the present study that c-myc amplification is a prominent feature in hypertetrasomic/ hypertetraploid tumors with p53 dysfunction, and that it can occur in the diploid stage of tumor development, prior to the appearance of p53 abnormalities in hypertetraploid cancers.…”
Section: Discussionmentioning
confidence: 99%